Gender equity and family decision-making patterns of the Aklanon mothers - Israel, Perlita R. (2007)
The study examined gender equity and decision-making patterns of the Aklanon rural mothers and their partners and determined the factors related to power in decision-making. The decision-making patterns in the family was ascertained in terms of the family-related activities such as parenting, educating family members, family budgeting, family nutrition and health; and in terms of family practices on spousal rights, benefits, obligations and opportunities. This study also examined the attitude of mothers towards gender equity and determined whether attitudes vary across various personal and family-related characteristics. Three hundred and eighty-eight (388) Aklanon mothers belonging to dual-earner households from eight selected municipalities in the province of Aklan responded to the researcher-made questionnaire. Twenty mothers, the top and lowest ten scorers in the gender equity scale were also interviewed to elicit qualitative data on their decision-making patterns. The frequency count, mean and percentages were used to quantify the profile of the rural mothers and level of gender equity in the family and community. Analysis of Variance (ANOVA) was used to find the significant correlation between mothers' profile and their attitude towards gender equity. Chi-square and averaging coefficient correlation were then applied. Findings revealed that majority of husbands and wives obtained college education; earned below Php 4,000.00 a month; aged between 30 to 49 years old; and regularly engaged in farming and fishing. Most of the families have only 1-3 children without other people living with them. Rural mothers have positive attitude towards gender equity in the family but less so in the community. Their attitude did not influence their decision-making patterns. There is gender equity in decision-making. Husbands and wives made joint decision in terms of parenting, educating family members, budgeting and family health and nutrition. The same trend was observed when making decisions on family practices. Both husbands and wives commonly enjoy rights, benefits, obligations and opportunities in the family. There was no significant difference found between mother's personal and family-related factors and their level of attitude towards gender equity in the family and community. Neither was significant correlation found between personal and family related factors and decision-making patterns of rural mothers. Rural mothers compared to their husbands, play a unique and more significant role in the family in terms of parenting, budgeting and educating family members. They are less dominant in the household but are not totally passive. Rural earning mothers have been found to have a voice in the family. They have accepted the situation where their husbands make the decisions but they also make negotiations in order to reach an agreement or compromise. Based on the findings, a training design on rural women's empowerment through decision-making in the family and community was conceptualized. The primary purpose of the course is to enhance rural women's decision-making skills.